Perancangan resort di Pulau Peucang, Taman Nasional Ujung Kulon, Banten - Nurul Iqbal; Tri Endangsih; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
Planning area of maritime tourism in Peucang Island, Ujung Kulon National Park, Banten. Designed with the aim of developing tourism in the surrounding area and providing opportunities for people living around the Ujung Kulon National Park, to increase economic income through tourism development. In tourism development activities, the community does not only play a role as beneficiaries, but must be able to become actors who encourage the success of tourism development on Peucang Island. The use of the tropical concept on the building because the location was in the beach area, so that buildings must be adapting to the environment having tropical climate. The applications of the concept of tropical on the building of the use of existing natural material around the location to make the building look in harmony with the surrounding environment